New teachers talk about their preparation to teach early literacy. Issue 2 (2nd July 2020) - Meeks, Linda; Madelaine, Alison; Stephenson, Jennifer
ABSTRACT: Individual telephone interviews with 11 Australian beginning teachers who were newly appointed, or seeking a teaching position, were used to explore their perceptions of their preparation to teach early reading. Interviewees provided self-ratings of preparedness and ability to teach early reading, information about their knowledge of early reading instruction and information regarding their opinions of the quality and content of their teacher education courses in relation to the teaching of beginning reading. The results indicate that most of the interviewees demonstrated inadequate knowledge of the subject-specific content of beginning reading and that they were generally critical of their preservice preparation, especially with regard to translating theory into classroom practice. These findings have serious implications for the quality of student learning in early years classrooms and for those students who struggle to learn.